STRATEGI GURU AGAMA ISLAM DALAM MENGINTERNALISASI MODERASI BERAGAMA SISWA KELAS V SDN AKKOR PALENGAAN PAMEKASAN - Ahmad Mahfudz; Ahmad Wiyono (Dewan Pendidikan Pamekasan, 2023)
Islam is a religion that highly upholds the values of religious moderation. However, unfortunately, this concept of moderation is not understood holistically by some groups so that you can find extremist Muslims here and there who lean right or left. Conditions like this are quite sad because they can divide the people and the unity of the Indonesian nation. As an anticipation, it is very necessary to internalize the values of religious moderation from an early age, for example from elementary school age. This is where it becomes important, the existence of an Islamic religious teacher makes breakthroughs and effective strategies so that students can easily understand the concept of religious moderation and practice it in everyday life as has been done by the Islamic religious education (PAI) teacher at SDN Akkor Palengaan Pamekasan . In this research, the type of research used is qualitative-descriptive. The aim of this research is to find out: 1) The strategies used by PAI teachers in internalizing religious moderation for Class V students, and, 2) the obstacles faced in internalizing religious moderation for Class V students at SDN Akkor Palengaan Pamekasan. The conclusion as a result of research conducted by researchers is: PAI teachers at SDN Akkor pay special attention to material relating to religious moderation by ensuring that all students understand certain strategies. After that, he supervised students in practicing it in their daily lives, for example students were taken shopping to the city of Pamekasan to introduce them to places of worship of other religions. Then, with the support of the school principal, he provided special guidance for Class V regarding religious moderation considering that they were entering adolescence and would face complex problems.